PENGARUH PROFITABILITAS, LEVERAGE, CASH POSITION, GROWTH DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN - Cisilia, Aimee; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The stockholders have desire in investing their investment is to gain high return one of the desires isdividend. There are several factors which give influence to the dividend policy, so that this research has beenconducted in order to test the influence of profitability (ROE), leverage (DER), cash position (CP), growth(TAG), and managerial ownership (MOWN) to the dividend policy (DPR). The population is all manufacturingcompanies which are listed in Indonesia Stock Exchange and the numbers of data are 142 data in 2012-2014. Thenumbers of samples are 16 companies which meet the criteria. The data analysis of this research has been carriedout by using multiple linear regressions in order to identify the independent variables which give influence tothe dependent variable. Based on the result of goodness of fit test the model is feasible and meet the fit criteria.The result of determination coefficient test has proven that the independent variables give influence to thedependent variable. The result of the hypothesis test shows that profitability and growth does not give anyinfluence to the dividend policy whereas leverage, cash position, and managerial ownership give influence to thedividend policy.